A Systematic Review of the Reliability and Validity of Behavioural Tests Used to Assess Behavioural Characteristics Important in Working Dogs - Brady, Karen; Cracknell, Nina; Zulch, Helen; Mills, Daniel Simon (Frontiers in Veterinary Science, 2018)
1. Abstract 1.1 Background Working dogs are selected based on predictions from tests that they will be able to perform specific tasks in often challenging environments. However, withdrawal from service in working dogs is still a big problem, bringing into question the reliability of the selection tests used to make these predictions. 1.2 Methods A systematic review was undertaken aimed at bringing together available information on the reliability and predictive validity of the assessment of behavioural characteristics used with working dogs to establish the quality of selection tests currently available for use to predict success in working dogs. 1.3 Results The search procedures resulted in 16 papers meeting the criteria for inclusion. A large range of behaviour tests and parameters were used in the identified papers, and so behaviour tests and their underpinning constructs were grouped on the basis of their relationship with positive core affect (willingness to work, human-directed social behaviour, object-directed play tendencies) and negative core affect (human-directed aggression, approach withdrawal tendencies, sensitivity to aversives). We then examined the papers for reports of inter-rater reliability, within-session intra-rater reliability, test-retest validity and predictive validity. 1.4 Conclusions The review revealed a widespread lack of information relating to the reliability and validity of measures to assess behaviour and inconsistencies in terminologies, study parameters and indices of success. There is a need to standardise the reporting of these aspects of behavioural tests in order to improve the knowledge base of what characteristics are predictive of optimal performance in working dog roles, improving selection processes and reducing working dog redundancy. Keywords: affect, behavioural tests, dogs, emotion, personality, reliability, temperament, validity